Georgia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2021)
A recovery from the Covid-19 pandemic now underway in Georgia has benefited from a recent pickup in external demand and substantial fiscal support. Significant exchange rate depreciation, global commodity price increases and supply constraints have contributed to inflationary pressures and provided impetus for the authorities to start tightening monetary policy during 2021. Credit growth slowed during the pandemic but has since picked up again. Household and firm indebtedness is relatively high reflecting rapid credit growth in recent years. Banks face elevated credit risks as they carry high exposure to unhedged borrowers in foreign currency, some of whom are facing debt-servicing difficulties due to the pandemic.